2017
DOI: 10.3389/fcimb.2017.00284
|View full text |Cite
|
Sign up to set email alerts
|

dsRNA Binding Domain of PKR Is Proteolytically Released by Enterovirus A71 to Facilitate Viral Replication

Abstract: Enterovirus 71 (EV-A71) causes hand, foot and mouth disease in young children and infants, but can also cause severe neurological complications or even death. The double-stranded RNA (dsRNA)-dependent protein kinase R (PKR), an interferon-induced antiviral protein, phosphorylates the regulatory α-subunit of the eukaryotic translation initiation factor 2 in response to viral infection, thereby blocking the translation of cellular and viral mRNA and promoting apoptosis. The cleavage of PKR after infection with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 50 publications
0
26
0
Order By: Relevance
“…SG formation is induced upon the activation of eIF2␣ kinases, such as PKR and PERK. While enterovirus infection induces PKR activation, leading to an increase in both phosphorylated PKR (p-PKR) and p-eIF2␣ levels (55,56), FMDV infection was shown to block the activation of this pathway (57), possibly via 3C pro -dependent lysosomal degradation of PKR (57). It has also been reported that the titers of FMDV LLV can be rescued in PKR knockout cells (58), hinting at a possible role for L pro in suppressing PKR signaling.…”
Section: Discussionmentioning
confidence: 99%
“…SG formation is induced upon the activation of eIF2␣ kinases, such as PKR and PERK. While enterovirus infection induces PKR activation, leading to an increase in both phosphorylated PKR (p-PKR) and p-eIF2␣ levels (55,56), FMDV infection was shown to block the activation of this pathway (57), possibly via 3C pro -dependent lysosomal degradation of PKR (57). It has also been reported that the titers of FMDV LLV can be rescued in PKR knockout cells (58), hinting at a possible role for L pro in suppressing PKR signaling.…”
Section: Discussionmentioning
confidence: 99%
“…However, this does not seem to be the case for enteroviruses. It has been reported that PKR and eIF2␣ are phosphorylated during infection with several enteroviruses (37,(56)(57)(58), indicating that the viruses do not block activation of the ISR. Consistently, we did not observe an effect of 2A pro on the phosphorylation of PKR and eIF2␣.…”
Section: Discussionmentioning
confidence: 99%
“…Under such a condition, the doublestranded RNA-dependent protein kinase PKR phosphorylates the regulatory α subunit of eukaryotic translation initiation factor 2 (eIF2α) to block translation of both cellular and viral mRNAs. After EV-A71 infection, 3C pro cleaves PKR to activate viral translation and replication [23]. Notably, a cleavage fragment of eIF5B, a product of viral 3C pro , can be substituted for eIF2 to deliver Met-tRNAi to the 40S ribosomal subunit, while eIF2α is phosphorylated and inactivated by viral infection [24].…”
Section: Inhibition Of Host Cell Translation After Ev-a71 Infectionmentioning
confidence: 99%